Volatility and the investment response - Aizenman, Joshua 1949-; Marion, Nancy Peregrim 1949- (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1996)
We use the World Bank decomposition of aggregate investment shares into their private and public components to test for the correlation between volatility and investment in a set of developing countries. We uncover a statistically significant negative correlation between various volatility measures and private investment, even when adding the standard control variables. No such correlation is uncovered when the investment measure is the sum of private and public investment spending. Indeed, public investment spending is positively correlated with some measures of volatility. We also use the new World Bank data to redo the Ramey and Ramey (1995) test for a correlation between investment and the standard deviation of innovations to a forecasting equation for growth. While Ramey and Ramey found no significant correlation using aggregate investment data, we find a negative and highly significant relationship between innovation volatility and private investment in developing countries. These findings suggest that the detrimental impact of volatility on investment may be difficult to detect using aggregate data.